DISTRIBUSI KECEPATAN PADA SALURAN MENIKUNG 180° DENGAN MATERIAL DASAR BERGERAK - , BAYU NUGROHO, Prof. Dr. Ir. Bambang Yulistiyanto ([Yogyakarta] : Universitas Gadjah Mada, 2012)
In cornering flow like a river, there is the phenomenon of morphological changes due to flow, which on the inside of the bend is deposition and the outer side is erosion. This is due to the helocoidal flow, the spiral-shaped flow is formed from the main flow and the secondary flow. Secondary flow is a flow on the transverse plane, which is formed from radial velocity and vertical velocity. Secondary flow near the base have a direction to the center of the bend, while the flow near the surface of the water away from the center of the bend. Previous experiments on the velocity distribution of speed on cornering line, but for cornering channel conditions, the basic contours erodible base is formed naturally by the flow has not been investigated. Experiments using the flume with a width of 0,5 m, 0,4 m high, 1,25 m centerline radius and 180° of bend angle. Granular base using river sand with a uniform gradation, which pass sieve diameter of 1,2 mm and retained on 0,8 mm diameter sieve. The bed formed naturally with constant discharge 23,307 l/s until equilibrium condition, a condition in which the granular particel at base is not moving. Velocity measurement made after equilibrium is reached with Acoustic Doppler Velocimeter (ADV), which has the advantage to measure the velocity in the three axes directions at one point simultaneously. Results of measurements of the bed contours of the channel after reaching equilibrium is erosion occurs in the middle to the outside cornering lines with maximum erosion occurs at an angle of 60°, while the deposition occurs on the inside with a maximum deposition at the end of the bend. Tangential and radial velocity curve in the channel varies with the angle and bend radius. The maximum tangential velocity at the beginning of the bend is on the inside of the bend and gradually (the angle bend) the velocity decrease until the end of the curve where the maximum tangential velocity occurs on the outside. Secondary flow grow, it reaches maximum at 60º which valued radial velocity 11,47 cm/s and then decrease to 120º and increase again after that until the end of bend. The results of calculations using the Rozovskii and Bowmeester equations are overestimate than measured maximum radial velocity to double with same data Rm/B = 2,5 and B/H = 3,125.